If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 6 = 3(4y + -5) Reorder the terms: 6 + 2y = 3(4y + -5) Reorder the terms: 6 + 2y = 3(-5 + 4y) 6 + 2y = (-5 * 3 + 4y * 3) 6 + 2y = (-15 + 12y) Solving 6 + 2y = -15 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. 6 + 2y + -12y = -15 + 12y + -12y Combine like terms: 2y + -12y = -10y 6 + -10y = -15 + 12y + -12y Combine like terms: 12y + -12y = 0 6 + -10y = -15 + 0 6 + -10y = -15 Add '-6' to each side of the equation. 6 + -6 + -10y = -15 + -6 Combine like terms: 6 + -6 = 0 0 + -10y = -15 + -6 -10y = -15 + -6 Combine like terms: -15 + -6 = -21 -10y = -21 Divide each side by '-10'. y = 2.1 Simplifying y = 2.1
| N-14=3h | | 6v+9=3(v+8) | | 4(X-4)=0v | | -100=-4g | | 2h-h+3h-3h=13 | | 3(n+8)=22+8n | | X^2+88=10x | | 4x+3(x+4)=-9 | | -4(x-5)=9x+33 | | 6(ab)3= | | -7(n-6)-3n= | | 4+5=-8 | | -7v+4(v+3)=21 | | 15=x+ax | | 4x-48=-5(x+6) | | 9j-2j-4j=15 | | X^2=16x-65 | | 9n^2-2n+6=3 | | 19v+6b= | | 3(k+4)-6k+4+4= | | y=25x^2+20x+4 | | -7v+4(u+3)=21 | | -7y-26=23 | | 8+84p=6+10p | | X^2+4+3y=(x-3)(x+5) | | 130+70+2x+2y=360 | | x^2-15x+13=0 | | -2(1-2y)-y=7 | | 3x+4b=18 | | 0.2x+0.3=0.5 | | 5.8+x+5.8+x/2+3(5.8+x)/2=246.20 | | -17a=-12a-65 |